Search for a new scalar resonance decaying to a Higgs boson and another new scalar particle in the final state with two bottom quarks and two photons in proton-proton collisions at TeV - Hayrapetyan,A; Makarenko,V; Tumasyan,A; Adam,W; Andrejkovic,JW; Benato,L; Bergauer,T; Dragicevic,M; Giordano,C; Hussain,PS; Jeitler,M; Krammer,N; et al. (Journal of High Energy Physics, 2025)
A search is presented for a new scalar resonance, X, decaying to a standard model Higgs boson and another new scalar particle, Y, in the final state where the Higgs boson decays to a pair, while the Y particle decays to a pair of photons. The search is performed in the mass range 240–1000 GeV for the resonance X, and in the mass range 70–800 GeV for the particle Y, using proton-proton collision data collected by the CMS experiment at TeV, corresponding to an integrated luminosity of 132 fb-1. In general, the data are found to be compatible with the standard model expectation. Observed (expected) upper limits at 95% confidence level on the product of the production cross section and the relevant branching fraction are extracted for the X ? YH process, and are found to be within the range of 0.05–2.69 (0.08–1.94) fb, depending on mX and mY. The most significant deviation from the background-only hypothesis is observed for X and Y masses of 300 and 77 GeV, respectively, with a local (global) significance of 3.33 (0.65) standard deviations.